2019
DOI: 10.1111/jog.14131
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of diaphragmatic ectopic pregnancy using ultrasound‐guided percutaneous microwave ablation

Abstract: Diaphragmatic ectopic pregnancy is a rare status during the perinatal period. We reported that a 24‐year‐old woman with diaphragmatic ectopic pregnancy successfully received ultrasound‐guided percutaneous microwave ablation. It found that beta‐human chorionic gonadotropin level decreased showing 1067, 311.3 and 118.4 mIU/mL within five postoperative days, and P level reduced from 3.64 to 1.59 nmol/L. Contrast‐enhanced ultrasonography image on the third day after ablation indicated that there was no enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is usually administered via systemic application or local injection, guided by either ultrasound (US) or hysteroscopy [ 26 , 27 , 28 ]. A recent case reported that US-guided microwave ablation may be an alternative treatment for ectopic pregnancies of the diaphragm [ 29 ]. A recent study showed that expectant management of tubal ectopic pregnancy was having higher clinical pregnancy (65.3%) and a feasible procedure within cut-off of serum β-HCG level 1745 mUI/mL and ectopic pregnancy mass size cut-off of 25 mm or smaller [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is usually administered via systemic application or local injection, guided by either ultrasound (US) or hysteroscopy [ 26 , 27 , 28 ]. A recent case reported that US-guided microwave ablation may be an alternative treatment for ectopic pregnancies of the diaphragm [ 29 ]. A recent study showed that expectant management of tubal ectopic pregnancy was having higher clinical pregnancy (65.3%) and a feasible procedure within cut-off of serum β-HCG level 1745 mUI/mL and ectopic pregnancy mass size cut-off of 25 mm or smaller [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, plain CT scan showed a high density mass beneath the subhepatic space. In the related literature, Qian et al [ 9 ] reported on the enhanced-CT finding of nodular lesions at the top of the right hepatic diaphragm. Kuai et al [ 10 ] reported a case of ectopic liver pregnancy that showed a mixed density lesion within the right liver lobe under the diaphragm on CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…The choices of treatment for ectopic pregnancy involve either a conservative nonsurgical approach (typically, methotrexate administration) or surgery. For example, Qian et al [ 9 ] reported a successful diaphragmatic ectopic pregnancy intervention using US-guided percutaneous microwave ablation, and Chen et al [ 13 ] described a diaphragmatic pregnancy case managed with laparoscopic management. In our case, the diaphragmatic pregnancy had ruptured, necessitating laparoscopic operation.…”
Section: Discussionmentioning
confidence: 99%
“…The microwaves produced by the system penetrate into targeted tissues causing its coagulative necrosis when the temperature increases [4][5][6]. In pregnancy, thus far MWA has been used to perform selective feticide in monochorionic diamnotic twin pregnancies [7,8] including cases of twin reversed arterial perfusion [8,9] and to treat successfully a rare case of diaphragmatic ectopic pregnancy [10]. All these procedures were performed with a transabdominal approach under US guidance, and most pregnancies were > 20 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%